2016
DOI: 10.1016/j.atherosclerosis.2016.05.031
|View full text |Cite
|
Sign up to set email alerts
|

BCG lowers plasma cholesterol levels and delays atherosclerotic lesion progression in mice

Abstract: BCG reduces plasma nonHDL-cholesterol levels and delays atherosclerotic lesion formation in hyperlipidemic mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…Vaccination with BCG accelerates atherosclerosis in rabbits fed a cholesterol-rich diet (69). In contrast, other studies have reported a protective effect in atherosclerosis-prone mice (100,131), which might be due to its cholesterol-lowering action. Perhaps most compelling are recent observations that nonmicrobial products, including lipoproteins that are known drivers of cardiovascular disease, can also induce trained immunity (Table 1).…”
Section: Figmentioning
confidence: 85%
“…Vaccination with BCG accelerates atherosclerosis in rabbits fed a cholesterol-rich diet (69). In contrast, other studies have reported a protective effect in atherosclerosis-prone mice (100,131), which might be due to its cholesterol-lowering action. Perhaps most compelling are recent observations that nonmicrobial products, including lipoproteins that are known drivers of cardiovascular disease, can also induce trained immunity (Table 1).…”
Section: Figmentioning
confidence: 85%
“…In line with this, a recent genome-wide H3K27ac chromatin immunoprecipitation sequencing (ChIP-seq) analysis showed that the gene encoding receptor of oxLDL which is a marker of atherosclerosis, as well as genes directly related to inflammation, are enriched with H3K27ac in monocytes upon BCG vaccination (22), indicating that these pro-atherogenic genes are primed for an activation state in BCG-trained monocytes which could in turn contribute to atherosclerosis. However, it is noteworthy that several additional studies showed opposite results, pointing toward a beneficial effect of BCG vaccination on ASCVD (56)(57)(58). For example, in a human epidemiological cohort study, children vaccinated with BCG only showed a hazard ratio of 0.36 to develop cardiovascular diseases (58).…”
Section: Bcg-induced Training Programmentioning
confidence: 99%
“…However, other data suggest that hyperlipidemic mice fed a high-cholesterol diet had a delayed atherosclerotic plaque formation 6 weeks following BCG injection. It is important to realize, though, that in these mice, the BCG administration significantly lowered non-HDL cholesterol levels [ 15 ].…”
Section: Trained Immunity As a Novel Mechanism Of Atherogenesismentioning
confidence: 99%